Acute Pancreatitis and Leukemoid Reaction as the Presenting Manifestation of Hemorrhagic Fever with Renal Syndrome: A Case Report - Zhong L; Shi H; Li H; Xiao L; Peng Q; Liu Z; Wu P; Mo X (Infection and Drug Resistance)
Lanlan Zhong,1 Huanyu Shi,2 Hang Li,3 Lu Xiao,4 Qianyi Peng,1 Zhiyong Liu,1 Ping Wu,2 Xiaoye Mo2 1Department of Critical Care Medicine, Xiangya Hospital, Central South University, Changsha, Hunan, 410008, People’s Republic of China; 2Department of Emergency, Xiangya Hospital, Central South University, Changsha, Hunan, 410008, People’s Republic of China; 3Department of Emergency, Pingxiang People Hospital, Pingxiang, Jiangxi, 337000, People’s Republic of China; 4Department of Emergency, The First Affiliated Hospital of Hunan University of Chinese Medicine, Changsha, Hunan, 410007, People’s Republic of ChinaCorrespondence: Xiaoye Mo; Ping Wu, Department of Emergency, Xiangya Hospital, Central South University, Changsha, Hunan, 410008, People’s Republic of China, Email moxiaoye@csu.edu.cn; xyyywp@163.comBackground: Hemorrhagic fever with renal syndrome (HFRS), caused by Orthohantavirus hantanense (HTNV) infection, is characterized by a range of symptom including fever, hemorrhage, and renal impairment. Acute pancreatitis and leukemoid reaction associated with HFRS have been less frequently reported.Case Presentation: A 20-year-old male presented with fever, dizziness, and gastrointestinal symptom, which progressed to acute pancreatitis and leukemoid reaction. Despite initial treatment, his condition worsened, necessitating transfer to a tertiary care facility. Upon admission, the patient exhibited signs of organ dysfunction, and laboratory tests confirmed leukocytosis and thrombocytopenia, with imaging suggestive of pancreatitis. HTNV antibody test results were positive.Discussion: This case illustrates the complexity of diagnosing HFRS when the disease presents atypically. The symptom that are shared with other conditions can lead to misdiagnosis. Treatment of HFRS patients requires a multidisciplinary approach, with particular attention to the timing and type of therapy to manage complications effectively.Conclusion: This report emphasizes the importance of recognizing atypical presentations of HFRS and the benefits of a prompt and comprehensive treatment strategy. Early diagnosis and a tailored therapeutic approach are crucial for improving patient outcomes in such rare and complex cases. The case underscores the necessity for clinicians to be vigilant for secondary symptom of HFRS, particularly in high-incidence regions, and the role of early diagnosis and treatment in improving outcomes.Keywords: hemorrhagic fever with renal syndrome, hantavirus, acute pancreatitis, leukemoid reaction